Polycystic ovary syndrome in obstructive sleep apnea-hypopnea syndrome: an updated meta-analysis - He, Jie; Ruan, Xia; Li, Jia (Frontiers in Endocrinology, 2024)
Background: Obstructive sleep apnea-hypopnea syndrome (OSAHS) is correlated with metabolic deterioration in patients experiencing polycystic ovary syndrome (PCOS). Women diagnosed with PCOS exhibit a heightened prevalence of OSAHS. This meta-analysis aims to assess the morbidity of OSAHS in women affected by PCOS and to examine the differences in metabolismrelated indicators between OSAHS-positive and OSAHS-negative in women with PCOS.A comprehensive literature analysis of OSAHS morbidity in women with PCOS was conducted, utilizing databases such as CNKI, EMBASE, PubMed, Web of Science, and Wanfang.A comparison was carried out between patients with OSAHS-positive and those with OSAHSnegative in terms of their clinical characteristics and metabolic differences. The search language included English and Chinese. The acquired data were analyzed by employing RevMan 5.2 and Stata 11.0. Continuous variables with the same units were combined and analyzed through weighted mean differences (WMDs) as effect sizes, while continuous variables with different units were combined and analyzed through standardized mean differences (SMDs) as effect sizes. A conjoint analysis was performed on the basis of I 2 value, using either a fixed effect model (I 2 ≤ 50%) or a random effect model (I 2 > 50%).Results: A total of 21 articles met the inclusion criteria for this study. The findings indicated that 20.8% of women with PCOS were found to have comorbid OSAHS. The subjects were categorized into various subgroups for meta-analysis on the basis of race, age, disease severity, body mass index (BMI), and diagnostic criteria of PCOS. The results revealed high morbidity of OSAHS in all subgroups. In addition, most metabolic indicators and parameters of metabolic syndrome were notably worse in women suffering from both PCOS and OSAHS in comparison to their counterparts solely diagnosed with PCOS.The current literature indicates higher morbidity of OSAHS among women with PCOS, linking OSAHS with worse metabolic status and obesity in this population. Consequently, clinicians are advised to prioritize the detection and management of OSAHS in women with PCOS.